PWE-055 The prevalence, clinical relevance and impact on diet of lactose intolerance in a population with lactase deficiency: a randomised, double-blind, dose response study in healthy subjects and patients with diarrhoea predominant irritable bowel syndrome. (28th May 2012) - Fox, M R; Yang, J; Deng, Y; Cong, Y; Fried, M; Dai, N
Abstract : Introduction: Lactose Intolerance (LI) is a common clinical syndrome; however there is a lack of high quality evidence about its epidemiology, diagnosis and clinical relevance in health and patients with functional gastrointestinal disease. Additionally the impact of LI on intake of dairy produce is uncertain because previous studies have often tested tolerance only at very high doses and/or failed to assess both self perceived and objective lactose tolerance. Aim: To assess the prevalence of LI in a population with lactose malabsorption and the effect of LI on intake of dairy products in healthy volunteers (HVs) and patients with diarrhoea predominant irritable bowel syndrome (D-IBS). Methods: A Chinese population known to have a high prevalence of lactase deficiency was studied. 60 D-IBS patients and 60 HVs underwent hydrogen breath test (HBT) at 10 g, 20 g, 40 g lactose on three test days in a randomised, double-blind three way cross-over study. Lactose Malabsorption (LM; H2 rise >20 ppm) and intolerance (LI ≥2 point rise on validated symptom score) were assessed at each dose. Genetic sequencing of the lactase gene promoter region was also performed. The impact of LI (both self-reported and from HBT) on lactose intake was assessed by dietary questionnaire. Results: LM was prevalent in HVs and D-IBS patients (93% vs 92% at 40 g lactose, p=0.73). LI prevalence was lower in HVs than D-IBS patients at 10 g (3% vs 18%, OR 6.51 (CI 1.38 to 30.8), p=0.008), 20 g (22% vs 47%, OR 3.16 (CI 1.43 to 7.02), p=0.004) and 40 g (68% vs 85%, OR 2.63 (CI 1.08 to 6.42), p=0.03). The genotype in all participants was C/C-13 910 and no other SNP was identified on gene sequencing of the lactase gene regulatory sequence. Most participants (83/120 (69%)) included milk and dairy products in their diet; however D-IBS patients reported less frequent intake of dairy products than HVs and a smaller amount of lactose in the diet (D-IBS: 9.0 g (4.5–17.3) vs HVs: 19.5 g (6.0–36.4); p=0.040). D-IBS patients also self-reported LI more frequently than HVs (63% vs 22%, OR 6.25 (CI 2.78 to 14.0), p<0.001); however, self-reports of LI did not predict results of objective HBT. Conclusion: The likelihood of LI is increased in patients with D-IBS, especially at low lactose doses. Self reported lactose intolerance, but not objective LI on HBT, was associated with avoidance of dairy products. Competing interests: M Fox Grant/Research Support from: Nestle International, J Yang: None declared, Y Deng: None declared, Y Cong: None declared, M Fried: None declared, N Dai: None declared.